Impacts et opportunités de la nouvelle gestion des inondations dans les domaines de la conception et de l’aménagement urbain - Émilie Gascon (Projets de Paysage)
A major change is underway in the management of urban flood risks. After an almost generalized resistance-based approach, the strategic vision of resilience is now being explored. This transition is interesting in that it transforms the way we look at water flows, but also raises once more the issue of the city as a floodplain territory in the 21st century. The urban planning response may be conceived of as a system involving three levels: technical and architectural considerations; the landscape; and water cities. Resulting from the analysis of projects, this system presents the advantage of considering the notion of water cities. These cities are remarkable because they tend to transcend flood risk management in urban planning by benefiting from and creating opportunities relating to water.